Classroom Assessment as a Diagnostic Tool: Identifying Students' Learning Difficulties in Arabic Language Subjects: Asesmen Kelas Sebagai Alat Diagnostik: Mengidentifikasi Kesulitan Belajar Siswa Pada Mata Pelajaran Bahasa Arab - Fadhel Izanul Akbar (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Classroom assessment plays a crucial role in identifying and addressing student learning difficulties. This enables teachers to design targeted interventions that improve learning outcomes. Classroom assessments, when aligned with the four Arabic language skills (maharah lughawiyyah), namely listening (istima’), speaking (kalam), reading (qiraah), and writing (kitabah), allow teachers to identify specific barriers in each skill area and plan targeted pedagogical interventions. This study aims to explore the effectiveness of classroom assessment as a diagnostic tool in identifying students' learning barriers in Arabic language subjects at the secondary school level. Using a qualitative approach, the study involved in-depth interviews with teachers to understand how assessments are used in identifying students' Arabic learning difficulties. The results show that classroom assessments can identify patterns of conceptual errors in grammar and sentence structure, as well as barriers to reading comprehension, and psychological factors such as anxiety and lack of motivation. Additionally, reflective and feedback-based assessments enable teachers to be more responsive in adjusting their teaching strategies. This study emphasizes that systematic and observation-based classroom assessment can be an effective diagnostic tool in supporting more adaptive Arabic language learning. The implications of this study offer valuable insights and recommendations for educators to integrate classroom assessment into a more responsive and evidence-based pedagogical approach. Keywords: Classroom Assessment, Diagnostic Tools, Learning Difficulties, Maharah Lughawiyah, Observation, Teaching Strategies